Prognostic value, localization and correlation of PD-1/PD-L1, CD8 and FOXP3 with the desmoplastic stroma in pancreatic ductal adenocarcinoma. - Diana, A; Wang, L; D'Costa, Z; Allen, P; Azad, A; Silva, M; Soonawalla, Z; Liu, S; McKenna, W; Muschel, R; Fokas, E (Impact Journals, 2016)
We examined the prognostic value of programmed cell death-1 (PD-1) and its ligand (PD-L1) together with CD8+ tumor-infiltrating lymphocytes (TILs) and FOXP3+ Tregs in resectable pancreatic ductal adenocarcinoma (PDAC) samples treated with adjuvant chemotherapy. Whole-mount FFPE tissue sections from 145 pancreatectomies were immunohistochemically stained for PD-1, PD-L1, CD8 and FOXP3. Their expression was correlated with clinicopathological characteristics, and overall survival (OS), progression-free survival (PFS), local progression-free survival (LPFS) and distant metastases free-survival (DMFS), in the context of stroma density (haematoxylin-eosin) and activity (alpha-smooth muscle actin) and in regard to intratumoral lymphoid aggregates. The median OS was 21 months after a mean follow-up of 20 months (range, 2-69 months). In multivariate analysis, high PD-1+ TILs expression was associated with better OS (p = 0.049), LPFS (p = 0.017) and DMFS (p = 0.021). Similar findings were observed for CD8+ TILs, whereas FOXP3 and PD-L1 lacked prognostic significance. Although TIL distribution was heterogeneous, tumors of high stroma density had higher infiltration of CD8+ TILs than loose density stroma and vice versa (p < 0.001), whereas no correlation was found with stromal activity. Sixty (41.4%) tumors contained lymphoid aggregates and the presence of PD-1+ TILs was associated with better OS (p = 0.030), LPFS (p = 0.025) and DMFS (p = 0.033), whereas CD8+ TILs only correlated with superior LPFS (p = 0.039). PD-1+ and CD8+ TILs constitute independent prognostic markers in patients with PDAC treated with adjuvant chemotherapy. Our study provides important insight on the role of PD-1/PD-L1 in the context of desmoplastic stroma and could help guide future immunotherapies in PDAC.